2007
DOI: 10.1001/archderm.143.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Response of Severe Mechanobullous Epidermolysis Bullosa Acquisita to Combined Treatment With Immunoadsorption and Rituximab (Anti-CD20 Monoclonal Antibodies)

Abstract: Background: Epidermolysis bullosa acquisita (EBA) is an autoimmune bullous disorder with mucocutaneous involvement, skin fragility, and tendency to scarring. The mechanobullous form of EBA has a chronic relapsing course and is difficult to treat. We describe herein the therapeutic response of 2 patients with recalcitrant mechanobullous EBA to combined treatment with immunoadsorption and rituximab, an anti-CD20 monoclonal antibody that induces depletion of B cells in vivo. Observations: Two patients with mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 65 publications
2
50
0
4
Order By: Relevance
“…14,25,31 Concominant systemic therapy used during rituximab treatment have included prednisone, dexamethasone, mycophenolate mofetil, azathioprine, cyclophosphamide, colchicine, methotrexate, 41 IVIg, plasmaphoresis, 42 daclizumab (anti-CD25 antibody), 34 and immunoabsorption. 13 As noted earlier, in this review we found 69.01% of autoimmune blistering patients treated with rituximab showed a complete response and 25.35% showed partial response. Collectively, 67 (94.37%) of patients showed clinical improvement.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…14,25,31 Concominant systemic therapy used during rituximab treatment have included prednisone, dexamethasone, mycophenolate mofetil, azathioprine, cyclophosphamide, colchicine, methotrexate, 41 IVIg, plasmaphoresis, 42 daclizumab (anti-CD25 antibody), 34 and immunoabsorption. 13 As noted earlier, in this review we found 69.01% of autoimmune blistering patients treated with rituximab showed a complete response and 25.35% showed partial response. Collectively, 67 (94.37%) of patients showed clinical improvement.…”
Section: Discussionsupporting
confidence: 69%
“…12 Niedermeier and colleagues also reported a patient with epidermolysis bullosa acquisita with complete remission after rituximab treatment, had clinical improvement which paralleled the decline of anti-basement membrane autoantibody titer. 13 Furthermore, Ahmed and colleagues and Schmidt and colleagues reported reduction of autoantibody titers during the treatment with combined rituximab and IVIg. 14,15 To what extent does the IVIg contribute to the autoantibody titer reduction is not clear and cannot be determined by the published data derived from this combined rituximab/IVIg study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plazmaferez ve immünadsorpsiyon, Goodpasture sendromu, myastenia gravis ve romatoid artrit gibi antikor aracılı hastalıkların tedavisinde kullanılmaktadır. Plazmaferez pemfigus vulgariste ilk kez 1978 yılında, immünadsorbsiyon ise PNP 1998 yılında kullanılmıştır 8 ; PF, büllöz pemfigoid 9 , pemfigoid gestasyones 10,11 , anti p-200 pemfigoidi 12 ve akiz epidermolizis bülloza 13 tedavisinde de kullanıldığına ilişkin yayınlar mevcuttur. Literatürde PV'de plazmaferez kullanımına dair mevcut olan tek kontrollü çalışma Guillaume ve ark.…”
Section: Discussionunclassified